2000
DOI: 10.1016/s0025-6196(11)64193-1
|View full text |Cite
|
Sign up to set email alerts
|

Anemia: A Cause of Intolerance to Thyroxine Sodium

Abstract: Usual causes of intolerance to thyroxine sodium include coronary artery disease, advanced age, untreated adrenal insufficiency, and severe hypothyroidism. We describe 4 patients with iron deficiency anemia and primary hypothyroidism. After treatment with thyroxine sodium, these patients developed palpitations and feelings of restlessness, which necessitated discontinuation of the thyroid hormone. After the anemia was treated with ferrous sulfate for 4 to 7 weeks, they were able to tolerate thyroxine sodium the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Iron is a component of many enzymes including thyroid peroxidase (TPO) which takes part in the initial two steps in thyroid hormone biosynthesis [11]. Low ferritin levels have also been observed in hypothyroid patients [12]. Several studies in animals and humans have shown that nutritional iron deficiency may significantly lower the circulating levels of both thyroxine and triiodothyronine and may also reduce conversion of T4 to T3 [13,14].…”
Section: Discussion:-mentioning
confidence: 99%
“…Iron is a component of many enzymes including thyroid peroxidase (TPO) which takes part in the initial two steps in thyroid hormone biosynthesis [11]. Low ferritin levels have also been observed in hypothyroid patients [12]. Several studies in animals and humans have shown that nutritional iron deficiency may significantly lower the circulating levels of both thyroxine and triiodothyronine and may also reduce conversion of T4 to T3 [13,14].…”
Section: Discussion:-mentioning
confidence: 99%
“…3 was bypassed by giving the patient a different LT4 product. If problems continue, refer the patient to an allergist to rule out other causes [118] [119] [120].…”
Section: Failure Of Therapymentioning
confidence: 99%
“…Additional iron substitution in subclinical hypothyroidism increases the effectiveness of L-thyroxine treatment. According to Shakir et al, in patients with anaemia the tolerance of L-thyroxine therapy may be worse [3]. Therefore, it is advised to initiate treatment with iron substitution, then add L-thyroxine.…”
Section: Hyperthyroidismmentioning
confidence: 99%